Renal threshold for glucose: physiological basis and relationship with water metabolism. A narrative review - Gozhenko, Anatoliy; Zukow, Walery; Olenovych, Olha; Gozhenko, Olena (Pedagogy and Psychology of Sport, 2026)
Background. The renal glucose threshold (RGT) is traditionally regarded as a passive consequence of sodium-glucose cotransporter type 2 (SGLT2) saturation in the proximal tubules of the nephron. However, this explanation addresses only the molecular mechanism, leaving unanswered the fundamental physiological question: why did evolution set this threshold precisely at 8–10 mmol/L? We propose that the answer lies not in the limitations of transport systems, but in the active protection of osmotic homeostasis and cellular hydration. Objective. To propose a new conceptual model of the RGT based on the priority of protecting cellular hydration over preserving glucose as an energy substrate, and to demonstrate the pathophysiological relationship between glycaemic regulation and water-electrolyte metabolism in diabetes mellitus. Methods. A narrative review of current literature on renal physiology, osmoregulation, molecular biology of glucose transporters, and clinical diabetology was conducted. The search was performed in the PubMed, Scopus, and Web of Science databases. Results. The RGT (8–10 mmol/L) mathematically corresponds to the upper limit of normal plasma osmolality (295 mOsm/kg). Glucosuria is a physiologically programmed protective mechanism that prevents critical hyperosmolality and protects cells from osmotic stress. In type 2 diabetes mellitus (T2DM), the adaptive increase in maximum tubular glucose reabsorption (Tm_G) and RGT is a pathological phenomenon contributing to chronic hyperglycaemia and cellular dehydration. SGLT2 inhibitors restore the physiological threshold and the protective mechanism of glucosuria. Studies of the osmoregulatory function of the kidneys during the development of experimental diabetes mellitus confirm impairment of urinary osmotic concentration already at the early stages of the disease (Olenovych et al., 2020; Olenovych & Zukow, 2022; Olenovych et al., 2025). Conclusions. The RGT is an evolutionarily formed mechanism for the protection of cellular hydration. Understanding this principle opens new perspectives for interpreting the pathophysiology of diabetes mellitus and the mechanisms of action of modern glucose-lowering drugs